Hydrothermal dewatering of a Chinese lignite and properties of the solid products. (15th September 2016) - Liao, Junjie; Fei, Yi; Marshall, Marc; Chaffee, Alan L.; Chang, Liping
Highlights: Lignite can be efficiently upgraded by hydrothermal dewatering (HTD) process. During HTD, organics and inorganics removed increase with HTD temperature. After HTD, the hydrophobicity of coal is higher and increases with HTD temperature. HTD coal has a higher spontaneous combustion tendency than the raw coal. Abstract: A lignite from Shengli mine in Chinese Inner Mongolia was upgraded by hydrothermal dewatering (HTD). The effects of the HTD process on the solid product yield and the removal rate of elements, organics and inorganics in this coal were determined. The moisture re-adsorption capacities and spontaneous combustion behaviors of coal products from the HTD process were studied, using the saturated salt solution and wire basket reactor methods respectively. FT-IR, XRD, CO2 adsorption, mercury intrusion porosimetry (MIP) and helium pycnometry were carried out to characterize the physicochemical properties of samples. The results show that during the HTD process, organic matter was removed due to the loss of CH3, CH2, and O-containing functional groups, while the inorganic matter was mainly removed in the forms of Ca- and Fe-containing minerals. The amounts of both organic and inorganic matter removed increased with temperature. The equilibrium moisture contents of the hydrothermally dewatered coals at 30 °C in the relative humidity range 11–97% were lower than those of the raw coal. They decreased as the HTD temperature rose, probably due to the increase in the loss of hydrophilic O-containing functional groups and decrease in surface area with the increasing of HTD temperature. Moreover, the critical ignition temperature ( Tcr ) of all the hydrothermally dewatered coals, as measured by wire basket spontaneous combustion experiments, was lower than that of raw coal.